1989
DOI: 10.1111/j.1699-0463.1989.tb00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous gastritis associated with Campylobacter pylori

Abstract: gastritis associated with Camp-vlobacrer pylori. APMIS 97:Three cases of granulomatous inflammation in gastric biopsies showing Campylobacter pylori infestation are described. This type of reaction to Campylobacterpylori has not previously been described, and occurred in I . 1% of gastric biopsies containing Campylobacter-like organisms (CLO), in this series of all gastric biopsies submitted for histological examination during one year. Two other cases each showed a mucosal granuloma: one was a patient with Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 6 publications
(4 reference statements)
2
27
0
Order By: Relevance
“…Hp infection of the gastric mucosa is frequently associated with nonspecific gastritis (5). Dhillon and Sawyerr first reported an association between granulomatous gastritis and Hp in 1989 (6). In our case, we showed the resolution of symptoms, endoscopic findings, and granulomatous gastritis after successful Hp eradication therapy.…”
Section: To the Editorsupporting
confidence: 62%
“…Hp infection of the gastric mucosa is frequently associated with nonspecific gastritis (5). Dhillon and Sawyerr first reported an association between granulomatous gastritis and Hp in 1989 (6). In our case, we showed the resolution of symptoms, endoscopic findings, and granulomatous gastritis after successful Hp eradication therapy.…”
Section: To the Editorsupporting
confidence: 62%
“…GG is an uncommon histological finding present in 0.08–0.35% of gastric biopsy samples,2 3 0.27% of biopsy samples from patients with gastritis,1 and 1.1% of samples from patients with H pylori gastritis 7. We conducted a retrospective study of 23 children and 23 adults with a final histological diagnosis of GG identified over a 7-year period to compare age-related differences in clinical and pathological features and to determine the prevalence of GG in a paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy persists with regard to the existence of ‘isolated’ or ‘idiopathic’ GG. One thought is that isolated GG is a well-described entity of unknown aetiology that may represent a non-specific reaction to a variety of unidentified agents 3 7. A competing thought is that isolated GG does not exist and that, with adequate long-term follow-up, an underlying aetiology could be determined 2…”
Section: Discussionmentioning
confidence: 99%
“…Maeng et al [2] noted that 88.9% of the 18 cases they reviewed were positive for H. pylori, indicating a possible association of granulomatous gastritis with H. pylori. Dhillon and Sawyerr [3] were the first to report successful treatment of H. pylori-associated granulomatous gastritis with bismuth. Miyamoto et al [4] reported two cases of idiopathic granulomatous gastritis that resolved with H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%